Determinants of Antiretroviral Treatment Success and Adherence in People With Human Immunodeficiency Virus Treated for Tuberculosis. (19th November 2022) - De Castro, Nathalie; Chazallon, Corine; N'takpe, Jean-Baptiste; Timana, Isabel; Escada, Rodrigo; Wagner, Sandra; Messou, Eugène; Eholie, Serge; Bhatt, Nilesh; Khosa, Celso; Laureillard, Didier; Do Chau, Giang; et al.
Abstract: Background: In people with human immunodeficiency virus [HIV] presenting with advanced disease, rates of virologic success may be lower than expected. The Reflate TB2 trial did not show non-inferiority of raltegravir versus efavirenz in people with HIV (PWH) treated for tuberculosis. We aimed to identify factors associated with virologic success and higher adherence in the trial. Methods: In this analysis, we included participants enrolled in the Reflate TB2 trial with adherence data available. The primary outcome was virologic success (HIV-1 ribonucleic acid [RNA] <50 copies/mL) at week 48, and the secondary outcome was adherence as assessed by the pill count adherence ratio. We used logistic regression to study determinants of virologic success and optimal adherence in 2 separate analyses. Results: Four hundred forty-four participants were included in the present analysis. Over the 48-week follow-up period, 290 of 444 (65%) participants had a pill count adherence ratio ≥95%. At week 48, 288 of 444 (65%) participants were in virologic success. In the multivariate analysis, female sex (adjusted odds ratio [aOR], 1.77; 95% confidence interval [CI], 1.16–2.72; P = .0084), lower baseline HIV-1 RNA levels (<100 000; aOR, 2.29; 95% CI, 1.33–3.96; P = .0087), and pill count adherence ratio ≥95% (aOR, 2.38; 95% CI, 1.56–3.62; P < .0001) were independently associated with virologic success. Antiretroviral pill burden was the only factor associated with pill count adherence ratio ≥95% (OR, 0.81; 95% CI, .71–.92; P = .0018). Conclusions: In PWH with tuberculosis receiving raltegravir or efavirenz-based regimens, female sex, optimal adherence, and baseline HIV-1 RNA <100 000 copies/mL were associated with virologic success, and the number of antiretroviral tablets taken daily was a strong predictor of adherence. Abstract : PWH with tuberculosis receiving raltegravir or efavirenz-based regimens, female sex, optimal adherence, and baseline HIV-1 RNA <100 000 copies/mL were associated with virologic success, and the number of antiretroviral tablets taken daily was a strong predictor of adherence.